Voices from the Classrooms: Student and Teacher Responses on English Assessment Exclusion from the National Assessment - Sianipar, Rafita Tioria; Rambe, Kartina Rahmadhani (Universitas Negeri Medan, 2024)
For many years, English has been a core subject in the National Examination (UN) across all levels of education, including Elementary, Junior High, and Senior High School. In 2020, the Indonesian Ministry of Education introduced a new policy that replaced the UN with the National Assessment, which aims to evaluate students' proficiency in literacy and numeracy skills. However, notably, the government has excluded English from the subjects assessed at the Junior High School level. Consequently, this study seeks to explore the perceptions of students and teachers regarding the omission of the English subject from the National Assessment. The research involved 3 English teachers and 43 students from a junior high school in Tebing Tinggi, North Sumatra, who had previously participated in the new assessment format. Data were gathered through questionnaires and interviews. Specifically, the questionnaire data were analysed using descriptive statistics, while the interview data underwent analysis through data reduction, data display, and conclusion drawing, as outlined by Miles, Huberman and Saldana (2014). The findings reveal that both students and teachers believe that English should be reinstated in the National Assessment. Additionally, the exclusion of English elicits contrasting sentiments; while the majority of students express dissatisfaction, the teachers predominantly feel a sense of relief. Ultimately, this article discusses several considerations concerning the implementation of the National Assessment.